2010
DOI: 10.1111/j.1600-0579.2009.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

A generic consensus assessment of undergraduate competence in forceps exodontia in the United Kingdom

Abstract: Using this generic checklist, it may now be possible to pool data inter-institution to perform more powerful analyses on how our students obtain, or fail to obtain competence in forceps exodontia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…In 2008, the minimum number of extractions that undergraduates were expected to achieve during their clinical years varied between 11 dental schools in the UK from 20 to 115. 15 Shortage of suitable cases for undergraduates 17 has been suggested to be one of the limits to develop confidence, 6 as the number of surgical extractions performed increased competence. 18 However, in another study, no significant relationship was observed between the total number of teeth extracted and the successful completion of the final assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, the minimum number of extractions that undergraduates were expected to achieve during their clinical years varied between 11 dental schools in the UK from 20 to 115. 15 Shortage of suitable cases for undergraduates 17 has been suggested to be one of the limits to develop confidence, 6 as the number of surgical extractions performed increased competence. 18 However, in another study, no significant relationship was observed between the total number of teeth extracted and the successful completion of the final assessment.…”
Section: Discussionmentioning
confidence: 99%
“…20 Only a small proportion of schools utilised pre-patient competency assessment in forceps exodontia with a scoring system to provide formative feedback on performance following clinical sessions. 7 The mean "target number" of extractions expected to be completed in 11 of the UK dental schools was 51, with the majority of this quota being achieved in years three and four. 4 Structural clinical operative tests (SCOTs) have been implemented in some dental schools; however, many students did not find these beneficial.…”
mentioning
confidence: 99%
“…looked at its application in education. 22 However, these studies clearly have a role in the design of educational courses, and allied specialties such as emergency medicine will benefit from the resultant concise and structured dissemination of knowledge supported by expert opinion.…”
Section: Discussionmentioning
confidence: 99%